Information System Audit Using Framework Control Objectives for Information and Related Technology (Cobit) on Values Processing Application for Online Student at Senior High School 14 of Bandar Lampung (SMA Negeri 14 Bandar Lampung) - Siti Zakiah (Journal of Applied Science, Engineering, Technology, and Education, 2022)
Senior High School 14 of BANDAR LAMPUNG is one of the Secondary Education that applies the use of information technology into the academic information system. The Secondary Education strategy plan in the development of information systems has not gone through the information system audit process so that the planning of the information system is not in line with the needs of the expected business process. To overcome this, it is necessary to have an academic information system audit to see the maturity level so as to produce an audit report that can be used as a recommendation in planning an academic information system in the future. An information system audit was conducted using the COBIT 4.1 framework on the DS11 domain. Data collection techniques through observation, interviews and questionnaires. The questionnaire used is a maturity level questionnaire while the maturity level questionnaire is used to measure the level of maturity of the information system for the current condition (as is) and the expected condition (to be). The results of the study concluded that the detailed control objective performance obtained from the expected maturity level (to be) questionnaire in the DS11 process as a whole was at level 4 or managed and measurable. Recommendations for planning solutions towards the expected level of maturity are carried out by defining remedial actions on the attributes of AC, PSP, TA, SE, RA and GSM